Approaches for the enhancement of reading as an interesting activity for kids from 5 to 10 years old - Mendoza Chavarría, María Elena; De Gracia, Edwar; Acosta, Jorge; Vargas, Víctor (David, Panamá : UDELAS, 2010)
Reading is one of the most interesting activities that everyone can enjoy. It does not matter if you are a little kid, a young person or an adult; reading is something that involves people of any age at any place and any place and any social status.
GENERAL INDEX Graphic index Thought Dedication Acknowledgement Introduction CHAPTER I. THE PROBLEM OF INVESTIGATION CHAPTER II. THEORETICAL FRAMEWORK 2. Approaches for beginners from 5 to 10 years old 2.1. Phonic approach 2.1.2. Look and say approach 2.1.3. Whole sentence reading approach 2.1.4. Language experience approach 2.1.5. Constructivist approach 2.2. Techniques to be used with different approaches 2.2.1. Techniques to be used with phonic approach 2.2.1.1. Linguistic technique 2.2.1.2. Word recognition technique 2.2.1.3. Sound-letter relation technique 2.2.1.4. Tongue twister technique 2.2.2. Techniques to be used with look and say approach And other more CHAPTER III. METHODOLOGICAL PROCEDURES CHAPTER IV. ANALYSIS AND RESULTS INTERPRETATION Conclusion Recommendation Bibliography Appendix
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés.
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA; READING -- TESIS DE LICENCIATURA; ESCUELA DE EDUCACIÓN SOCIAL Y ESPECIAL; LICENCIATURA EN INGLES